EFFECT OF LOCALLY SOURCED NIGERIAN GYPSUM ON THE STRENGTH AND MICROSTRUCTURE OF PORTLAND CEMENT MORTAR (Nigerian Journal of Technology, 2020)
The objective of this study was to investigate the suitability of Nigerian, sourced Gypsum for the manufacture of Portland cement. Gypsum samples were obtained from eighteen deposits across Nigeria. These were classified into five purity groups based on their calcium sulphate content.  Foreign Gypsum, imported from Morocco, was used as control. Six cement samples where produced for each of the five Gypsum purity groups by grounding and blending cement clinker with 3%, 4%, 5%, 6% and 7% Gypsum content. The group 1 cement mix (having not more than 65% calcium sulphate content) has displayed flash set and could not be moulded and therefore not used for further analysis. Cement mortar prisms were produced for the groups 2, 3, 4 and 5 cement mixes, and subjected to flexural and compressive strength tests at 7, 14, 21 and 28 day curing periods. The cement mortar prisms were also subjected microstructure analysis at 7 and 28 days curing period. The spongy, gel and whitish colouration observed from the microstructure of the specimens indicated silicates enriched regions which have proven the strength increase from 7 to 28 day curing period. The optimum gypsum content of 5.5% was recommended. The results show that all but the class one gypsum with less than 65% purity content are suitable for cement manufacture. http://dx.doi.org/10.4314/njt.v39i4.5